Prisoners of the past South African democracy and the legacy of minority rule - Friedman, Steven 1953- (Wits University Press, 2021)
Building on the work of economic historian Douglass North and Ugandan political scholar Mahmood Mamdani, Friedman argues that the difficulties besetting South African democracy are legacies of the past, not products of the post-1994 era
Keywords: Geschichte 1994-; Democracy / South Africa / History / 20th century; Wirtschaftswachstum; Demokratie; Politischer Wandel; Sozialer Wandel; South Africa / History / 1994-; South Africa / Politics and government / 1994-; Südafrika